EDITORIAL - Kadankavil, Thomas (Journal of Dharma, 1988)
Religions claim to stand for upholding human dignity. Christians so proudly quote St Paul to show that it is a crime for Christians to discriminate between the members of the human race. 'There is neither Jew nor Greek, there is neither bond nor free, there is neither male nor female: for ye are all one in Christ Jesus" (Gal 3:28). This oneness of all in Christ is compared to the unity of the body with diversities of operations. "For as the body is one, and hath many members, and all the members of that one body, being many, are one body, so also is Christ" (1Cor 12 :12). The Hindu culture also recognized the basic equality of men and women. "Where females are honoured there deities are pleased" (Manu Smrti III, 56). . But in agreement with another instruction of Manu, subjugation of women to men became the normal style of life in Indian society. "Her father protects her in childhood; her husband protects her in youth; her sons protecf her in old age; a woman is never fit for independence" (IX 3). The enlightened women in India today revolt against this tradition and they think that they are bound in slavery by the chains forged by men and is caught in the deathtrap of religion, thanks to lack of education and opportunities for public life.